Method of structure identification for interval difference operator based on the principles of honey bee colony functioning - Porplytsya, Nataliya; Dyvak, Mykola; Dyvak, Taras (Publishing House of Lviv Polytechnic National University, 2014)
In the article, the problem of structure identification of the interval difference operator (IDO) as a model of distributed parameters object is considered. A new method of structure identification of the IDO based on the foraging behavior of a honey bee colony has been proposed and verified. In addition, a neural-like computational scheme of the implementation of the method has been developed. The effectiveness of using the proposed method and its computational scheme are shown on the example of building a macromodel for the prediction of humidity distribution on a drywall sheet in the process of its drying. Розглянуто задачу структурної ідентифікації інтервального різницевого оператора (ІРО) як моделі об’єкта з розподіленими параметрами. Запропоновано та обґрунтовано новий метод структурної ідентифікації ІРО на основі харчової поведінки колонії медоносних бджіл. Крім того, розроблено нейроподібну схему реалізації зазначеного методу. Ефективність застосування запропонованого методу та його обчислювальної схеми проілюстровано на прикладі побудови макромоделі процесу розподілу вологості на поверхні листа гіпсокартону на стадії його сушіння.
Метод структурної ідентифікації інтервального різницевого оператора на основі принципів функціонування колонії медоносних бджіл
Keywords: structure identification; interval difference operator; artificial bee colony algorithm; interval data